2007
DOI: 10.1002/marc.200600729
|View full text |Cite
|
Sign up to set email alerts
|

Chemical One Step Method to Prepare Polyaniline Nanofibers with Electromagnetic Function

Abstract: A “Chemical one step method” (COSM) is proposed to prepare electromagnetic functional composite nanofibers of polyaniline (PANI/γ‐Fe2O3) having a diameter of ≈20 nm. In this approach FeCl3 is acts as the oxidant either for polymerization of aniline or for preparation of γ‐Fe2O3 magnets. Besides, it also provides protons produced by the hydrolysis process for doping PANI. It is found that the composite nanofibers have a high conductivity (10−1 ∼ 100 S · cm−1) and super‐paramagnetic properties (Ms = 0.46 ∼ 6.03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…The bands at 1304 and 1241 cm -1 can be assigned to C-H stretching vibration with aromatic conjugation [42,43]. The absorption peak near 1147 cm -1 results from the N-Q-N (Q denotes quinoid ring) stretching mode and is an indication of electron delocalization in PANI [44].The aromatic C-H out-of-plate deformation in 1,4-disubstituted benzene rings locates at 822 cm -1 . The absorption bands at 3379, 555, 1631, 1514, and 1313 cm -1 in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The bands at 1304 and 1241 cm -1 can be assigned to C-H stretching vibration with aromatic conjugation [42,43]. The absorption peak near 1147 cm -1 results from the N-Q-N (Q denotes quinoid ring) stretching mode and is an indication of electron delocalization in PANI [44].The aromatic C-H out-of-plate deformation in 1,4-disubstituted benzene rings locates at 822 cm -1 . The absorption bands at 3379, 555, 1631, 1514, and 1313 cm -1 in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Based on the above ideas, electromagnetic functional PANI-g-Fe 2 O 3 fibers were successfully prepared by a one-step method. [75] The trick to this method was to adjust the concentration of Fe 3þ and Fe 2þ and the molar ratio of aniline to APS. Interestingly, the electrical properties are controlled by the concentration of Fe 3þ ions, whereas the ferromagnetic properties are adjusted by the concentration of the Fe 2þ ions.…”
Section: Multi-functionality Based On a Templatefree Methods Associatementioning
confidence: 99%
“…Chiou et al have reported a successful synthesis of a highly uniform, relatively long PANI-NFs via a self-assembly process assisted by the presence of excess oxidant (APS), without the use of any acid in the initial step [199]. A chemical one-step method, which represents a modified dopant-free template-free method, has been proposed to prepare electromagnetic functional composite PANI/Fe 3 O 4 nanofibers, with a diameter of 20 nm, which show high conductivity and super-paramagnetic properties [202]. 3-D rose-like microstructures of PANI, which are self-assembled from 2-D nanosheets consisting of 1-D nanofibers, were synthesized by the dopant-free template-free method in the presence of APS as both oxidant and dopant under a high relative humidity of 80% [201].…”
Section: Rapid-mixing Methodmentioning
confidence: 99%